The Influence of Organizational Behavior, Communication and Self-Efficacy on the Performance of Government Internal Supervision Apparatus in the Riau Islands Province with Motivation as an Intervening Variable - TJATOER, Fadliyah Anas; WIBISONO, Chablullah; CATRAYASA, I Wayan (International Journal of Environmental, Sustainability, and Social Science, 2024)
In carrying out the duties and obligations mandated by the State Civil Apparatus (ASN), they must perform optimally, especially in public services. This is because the State Civil Apparatus (ASN) is a public servant who has sworn to be loyal to the state and serve the community's needs. The combined research model (Mixed Method) consists of a sequential explanatory model, a sequential exploratory model, a concurrent triangulation design, and a concurrent embedded model. The sequential explanatory model combines quantitative and qualitative research sequentially, first conducting quantitative research and then conducting qualitative research. The population in this research is the Government Internal Supervision Apparatus (APIP) throughout the Riau archipelago, both provincial regional inspectorates and city district inspectorates. With a total of 244 Government Internal Oversight Apparatus (APIP), using the Slovin formula, a sample of 151 was obtained. The results of the data analysis findings in discussion and hypothesis testing can be concluded as follows: The research demonstrates that Organizational Behavior, Communication, and Self-Efficacy significantly impact both Motivation and Performance. The mixed-methodology study suggests that to optimize the Government Internal Oversight Apparatus (GIOA) performance, leadership should regularly provide motivation, as it boosts enthusiasm and work efficiency among GIOA.